2023
DOI: 10.1038/s41598-023-49896-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of perfusion impairment in degenerative cervical myelopathy beyond the site of cord compression

Anna Lebret,
Simon Lévy,
Nikolai Pfender
et al.

Abstract: The aim of this study was to determine tissue-specific blood perfusion impairment of the cervical cord above the compression site in patients with degenerative cervical myelopathy (DCM) using intravoxel incoherent motion (IVIM) imaging. A quantitative MRI protocol, including structural and IVIM imaging, was conducted in healthy controls and patients. In patients, T2-weighted scans were acquired to quantify intramedullary signal changes, the maximal canal compromise, and the maximal cord compression. T2*-weight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A recently published study that used spinal cord perfusion MRI in different white matter tracts also suggested perfusion impairment predominantly in the ventral areas of the spinal cord 27 .…”
Section: Discussionmentioning
confidence: 93%
“…A recently published study that used spinal cord perfusion MRI in different white matter tracts also suggested perfusion impairment predominantly in the ventral areas of the spinal cord 27 .…”
Section: Discussionmentioning
confidence: 93%
“…Of note, a clinical study has investigated perfusion impairment in patients with degenerative cervical myelopathy compared to healthy subjects, using the current IVIM protocol 49 . The results showed a significant decrease in 𝐷 * and 𝐹 • 𝐷 * , with an average difference of -9.5% and -15.9% in the white matter and -11.0 % and -14.4% in the grey matter, respectively, at the group level (29 DCM patients, 30 healthy subjects), using the voxel-wise one-step fit.…”
Section: Comparing One-step and Two-step Fitting Algorithmsmentioning
confidence: 99%